Bullying and social skills in adolescents of two state educational institution in Ate - Alvarez Mendoza, Katherine Fiorella (2016)
The objective of this research was to determine the relationship between bullying and social skills in students from two educational institutions in the district of Ate. Questionnaire on bullying and bullying Checklist and social skills was applied. The sample consisted of 1,000 students aged between 11 and 14 years. The research was correlational, transactional descriptive and non-experimental design. The results show that there is significant relationship between role in bullying and social skills in adolescents.